2018
DOI: 10.2147/iprp.s117118
|View full text |Cite
|
Sign up to set email alerts
|

Role of pharmacists in providing parenteral nutrition support: current insights and future directions

Abstract: BackgroundParenteral nutrition (PN) therapy is a complex and critical therapy that requires special clinical knowledge, skills, and practice experience to avoid errors in prescribing, compounding, and clinical management of patients. Pharmacists with adequate clinical training and expertise in PN therapy can have pivotal role in the care of patients receiving PN therapy.ObjectiveThe aim of this systematic review was to describe and evaluate the different roles of pharmacists and their provided services related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
20

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 61 publications
(161 reference statements)
0
30
0
20
Order By: Relevance
“…The present study found that only about half of the students heard about the clinical pharmacy in their institutions during their study period. This may be due to absence of patient-oriented PharmD programs (Baniasadi et al, 2014;Bryant et al, 2009;Katoue, 2018;Stemer and Lemmens-Gruber, 2011). Also, a large proportion of the students agreed that HCPs will accept the pharmacists to provide additional services within the framework of clinical pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that only about half of the students heard about the clinical pharmacy in their institutions during their study period. This may be due to absence of patient-oriented PharmD programs (Baniasadi et al, 2014;Bryant et al, 2009;Katoue, 2018;Stemer and Lemmens-Gruber, 2011). Also, a large proportion of the students agreed that HCPs will accept the pharmacists to provide additional services within the framework of clinical pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…When the gastrointestinal tract is dysfunctional or inaccessible (cannot initiate enteral nutrition, necrotizing enterocolitis, gastrostomy), parenteral nutrition (PN) is used. PN formulations are complex admixtures that consist of multiple components, including both macronutrients (amino acids, lipids and dextrose) and micronutrients (electrolytes, vitamins, and trace elements) [3]. The importance of nutritional support for preterm neonatal outcomes is becoming increasingly accepted [4].…”
Section: Introductionmentioning
confidence: 99%
“…Based on best of our knowledge; there is no study occurred at Saudi Arabia, the Gulf, or Middle Eastern countries. [9] Therefore, the goal of this study was to explore the impact of the clinical outcome of pharmacist intervention through Total Parenteral nutrients at the public hospital in Riyadh city, Kingdom of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%